Incidental findings in low dose CT lung cancer screening of high-risk smokers: Results from the Manchester lung Health Check pilot. (November 2022) - Bradley, P.; Bola, B.M.; Balata, H; Sharman, A.; Booton, R.; Crosbie, P.A.J.
Highlights: The clinical significance of incidental findings in screening is poorly understood. Individuals at risk of lung cancer are also at higher risk of other pathologies. In this pilot (n = 1, 409), 11.4 % had incidental findings, including 5 malignancies. Cost-effectiveness implications should be considered during screening implementation. Abstract: Here we report the prevalence of incidental findings (IF) in the Manchester Lung Health Check pilot, which delivered mobile low-dose CT targeted lung cancer screening. 187 IFs were reported in 158 participants (11.2 % of individuals screened; n = 1, 409). 101 IFs in 90 participants (6.4 %) were concerning for extra-pulmonary malignancy. IFs resulted in 118 imaging studies, 20 invasive investigations, and 106 new diagnoses, including 5 malignancies (0.35 %). Clinical management of IFs required 84 specialist reviews (6.0 %), 34 medication changes (2.4 %) and 10 interventional treatments (0.71 %). Lung cancer screening detects clinically relevant IFs but further research is needed to better understand the potential benefits and harms of such findings to participants.